Teacher Recognition & Profesionalisme - W. Ahmad, W. Mohd Rashid (Penerbit UTHM, 2004)
This book aims to draw attention to literature on the aspects of teacher recognition of effectiveness and professionalism. Discussions are based on literatures and findings extracted from a research done by the author on Management of Staff Development Programmes At Technical Institutions in Malaysia. The first section seeks to describe the characteristics of the ‘effective teacher’, featuring their roles and commitment to the proffesion and the society. This hopefully will enable us to establish a clearer picture of the diversity of perception found on what recognition and professionalisme means.